Improving the Initial Reading Skills of Group B3 Children Though Busy Book Media at TK ABA Karangkajen - Utami, Dian (Ilmu Informasi Perpustakaan dan Kearsipan, 2024)
This study aims to improve the initial reading skills of group B3 children through busy book media at ABA Karangkajen Kindergarten. This research is a classroom action research using the Kemmis and Mc Taggart cycle model which is carried out collaboratively. The research subjects were class B3 children aged 5-6 years, totaling 16 children in TK ABA Karangkajen. The object of this research is the ability to read the beginning. Data collection techniques were carried out by interviews, observation and documentation. The data analysis technique in this study is to use qualitative and quantitative descriptive analysis. The results of the study show that the use of busy book media can improve the beginning reading ability of B3 graders. The increase in initial reading ability was shown by the results in the pre-action stage of 50%, after being given the action in the first cycle it increased to 65.63%, which means an increase of 15.63% from the pre-cycle. After being given another action in the second cycle, it increased to 82.25%, which means an increase of 17.19%.